Pengaruh Elemen Visual merchandising digital (Tampilan Layout, Desain visual, dan Branding digital) Terhadap Minat Beli Generasi Z Pada Platform Shopee - Muhammad Faisal Ardiansyah; Misti Hariasih; Satrio Sudarso (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The rapid growth of e-commerce has encouraged digital platforms to provide visually appealing shopping experiences in order to increase consumer interest. This study aims to analyze the influence of digital visual merchandising elements consisting of layout display, visual design, and digital branding on Generation Z’s purchase intention on the Shopee platform. This research employed a quantitative approach involving 150 Generation Z respondents in Sidoarjo Regency through questionnaire distribution. Data analysis was conducted using the PLS-SEM method with SmartPLS 3.0. The results indicate that all three variables have a positive and significant effect on purchase intention. However, based on the effect size value, layout display and visual design have relatively weak effects, while digital branding is the most dominant variable with the strongest influence. These findings highlight the importance of optimizing digital visual elements in increasing consumer purchase intention.